Precipitation in stretched Al-Cu-Mg alloys with reduced alloying content studied by DSC, TEM and atom probe - Gao, N; Davin, L; Wang, S; Cerezo, A; Starink, M (2002)
The hardening and microstructural evolution during ageing of a Al-1.2Cu-0.5Mg and a A1-1.2Cu-1.2Mg (at.%) alloy has been investigated. Artificial ageing at 150degreesC of stretched and naturally aged samples initially (up to about 48 h) leads to very limited further strengthening, but ageing at 190degreesC results a quick increase in strength. Detailed microstructural investigation using differential scanning calorimetry, transmission electron microscopy and three-dimensional atom probe demonstrated that hardening at 150degreesC is mostly dominated by the formation of solute clusters with varying compositions and plate-like zones rich in copper at early stages of ageing (t<24h) and by the formation of S phase at the later stages of ageing. At higher 190degreesC no zones or clusters form and the ageing is dominated by the formation of S precipitates.